2006
DOI: 10.1007/s00586-005-0019-2
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of complete C2–C3 dislocation with mild neurological symptoms

Abstract: The authors report a rare case of complete C2–C3 dislocation with unexpectedly mild neurological symptoms in a 57 year old man involved in a motor vehicle accident, who had previously undergone posterior laminectomy from C3 through C7. A retrospective chart analysis and a thorough radiographic review were performed. X-rays and CT of the cervical spine demonstrated a complete dislocation at the C2–C3 level. Computed tomographic angiography revealed disruption of both vertebral arteries; however, blood flow was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The patient was reduced with cervical traction without incident and then underwent anterior-posterior stabilization. 1,14 Finally, in a presentation most similar to ours, Shah and Rajshekhar report a traumatic C7-T1 spondyloptosis with mild quadraparesis. Similar to our case, the patient had fractures of C5, C6, and C7 lamina, which prevented dorsal compression of the spinal cord.…”
Section: Discussionmentioning
confidence: 70%
“…The patient was reduced with cervical traction without incident and then underwent anterior-posterior stabilization. 1,14 Finally, in a presentation most similar to ours, Shah and Rajshekhar report a traumatic C7-T1 spondyloptosis with mild quadraparesis. Similar to our case, the patient had fractures of C5, C6, and C7 lamina, which prevented dorsal compression of the spinal cord.…”
Section: Discussionmentioning
confidence: 70%
“…7,24 The symptoms and neurological signs may not correlate with the degree of bone injury. 20 Fountas et al 9 reported that the diameter of the cervical spinal cord is 15%-20% smaller than the diameter reported based on autopsy studies and considered that this relatively small diameter made the spinal cord less susceptible to injury by compression. This is probably the reason for the minor neurological deficits observed in our cases, together with auto decompression of the spinal canal.…”
Section: Discussionmentioning
confidence: 95%
“…However, the junction of these forms a unique zone of C2 and C3. Traumatic C2-3 dislocation is usually seen in the sagittal plane and is often associated with C2 pars interarticularis fracture [1][2][3]5]. This sagittal C2-3 dislocation can be translational or angular.…”
Section: Discussionmentioning
confidence: 99%
“…The traumatic C2-3 dislocations, including complete subluxation, have been described in the antero-posterior plane [1]. These have been classified further based on the stability and fracture morphology.…”
Section: Introductionmentioning
confidence: 99%